Electrocatalyst of PdNi Particles on Carbon Black for Hydrogen Oxidation Reaction in Alkaline Membrane Fuel Cell - Carolina Silva-Carrillo; Edgar Alonso Reynoso-Soto; Ivan Cruz-Reyes; Moisés Israel Salazar-Gastélum; Balter Trujillo-Navarrete; Sergio Pérez-Sicairos; José Roberto Flores-Hernández; Tatiana Romero-Castañón; Francisco Paraguay-Delgado; Rosa María Félix-Navarro (Nanomaterials)
This work reports the synthesis of PdNi bimetallic particles and Pd on Carbon black (Vulcan XC-72) by reverse microemulsion and the chemical reduction of metallic complexes. The physicochemical characterization techniques used for the bimetallic and metallic materials were TGA, STEM, ICP-OES, and XRD. Also, the electrocatalysts were studied by electrochemical techniques such as anodic CO stripping and β-NiOOH reduction to elucidate the Pd and Ni surface sites participation in the reactions. The electrocatalysts were evaluated in the anodic reaction in anion-exchange membrane fuel cells (AEMFC) and the hydrogen oxidation reaction (HOR) in alkaline media. The results indicate that PdNi/C electrocatalysts exhibited higher electrocatalytic activity than Pd/C electrocatalysts in both the half-cell test and in the AEMFC, even with the same Pd loading, which is attributed to the bifunctional mechanism that provides OH- groups in oxophilic sites associated to Ni, that can facilitate the desorption of Hads in the Pd sites for the bimetallic material.